Victims Business Body Shaming In Responding to Social Reality - Oktafiani, Fitri; Hardi, Emeliya; Denis, Sourbron (International Journal of Research in Counseling, 2022)
The body is the main part of physical appearance that can be seen and is very easily assessed by oneself and even by others. Body shaming is the act or practice of embarrassing someone by making comments mocking or criticizing someone about their body shape and size. The method used in this paper is descriptive qualitative method with direct data collection. The data obtained will be described in writing according to what the author got. The results of the study show that the efforts of victims of body shaming in responding to social reality, the first positive response to victims of body shaming is that victims respond with a smile, with a sense of humor, respond with an indifference attitude and do not take it seriously. The two negative responses to victims of body shaming are that victims are angry, offended, and unable to accept criticism from other people.